EXAMINING GENDER INEQUALITY THROUGH A LEGAL AND SOCIOLOGICAL PERSPECTIVE: IMPLICATIONS FOR SUSTAINABLE DEVELOPMENT: MENGKAJI KETIDAKSETARAAN GENDER MELALUI PERSPEKTIF HUKUM DAN SOSIOLOGI: IMPLIKASI TERHADAP PEMBANGUNAN BERKELANJUTAN - Oman Sukmana; Ikhwan Ridwan; Hardianto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The aim of the research is to examine in depth how gender inequality manifests in the dimensions of Law and Sociology, as well as its implications for the achievement of sustainable development. Her main focus is to analyze the complex interactions between formal legal frameworks and social norms in society, which are often the basis for the sustainability of discriminatory practices. The narrative literature review method was chosen to provide an in-depth and comprehensive analysis of various literatures, allowing the synthesis of previous research findings as well as the identification of knowledge gaps relevant to the topic being studied. The narrative literature review method is very suitable for exploring the complexity of gender inequality through the lens of Law and Sociology, as it allows the tracing of narratives and arguments that develop in a wide body of science. Overall, an in-depth analysis of the existing literature shows that gender inequality has a significant multidimensional impact on various aspects of sustainable development, ranging from economic, social, to environmental. This research explicitly shows that without a fundamental solution to gender disparities, progress towards the Sustainable Development Goals will be hampered.